أثر الاحتراق النفسي على مستوى الأداء للمحاسبين العاملين لدى وزارة المالية الفلسطينية في قطاع غزة - رشوان, عبد الرحمن (Université de M'sila, 2019)
هدف البحث إلى التعرف إلى طبيعة الاحتراق النفسي وتأثيره على مستوى الأداء للمحاسبين العاملين لدى وزارة المالية الفلسطينية في قطاع غزة، وأعتمد الباحث على المنهج الوصفي التحليلي، كما تم استخدم الاستبانة كأداة لجمع المعلومات ذات الصلة بمشكلة البحث الاستبانة، وقد تم توزيع هذه الاستبانة بعد إخضاعها لعملية التقييم والتحكيم من قبل عدد من المتخصصين، ومن ثم وزعت على عينة البحث التي تكونت من المدراء الماليين ورؤساء الاقسام والمحاسبين العاملين لدى وزارة المالية الفلسطينية في قطاع غزة والبالغ عددهم (160) محاسب ومحاسبة. كما أثبتت نتائج البحث أن قيمة الرواتب والحوافز والمكافآت التي يحصل عليها المحاسبين في وزارة المالية الفلسطينية غير مناسبة مع حجم الأعمال المبذولة، والتي تعد سبباً في تزايد حالة الاحتراق النفسي، وشعور المحاسبين بزيادة المهام والواجبات الملقاة على عاتقهم، وشعورهم بالإحباط بسبب عدم تقدير جهودهم من قبل المسئولين. كما أوصى البحث بضرورة زيادة نسبة الرواتب الذى يتقاضاها المحاسبين العاملين لدى وزارة المالية الفلسطينية لأنها متدني ولا تتناسب مع متطلبات المعيشة والوضع الاقتصادي السائد في قطاع غزة، وذلك للحد من ظاهرة الاحتراق النفسي ورفع مستوى الأداء لدى المحاسبين الكلمات المفتاحية: الاحتراق النفسي، مستوى الأداء، وزارة المالية الفلسطينية. Abstract: The objective of the research was to identify the nature of psychological combustion and its effect on the level of performance of accountants employed by the Palestinian Ministry of Finance in the Gaza Strip. The researcher relied on the analytical descriptive method. The questionnaire was used as a tool for collecting information related to the problem of the questionnaire. Evaluation and arbitration by a number of specialists, and then distributed to the sample of the research that consisted of financial managers and heads of departments and accountants working in the Palestinian Ministry of Finance in the Gaza Strip and the number of (160) accountant and accounting. The results of the research also showed that the value of salaries, incentives and bonuses received by the accountants in the Palestinian Ministry of Finance is not appropriate with the volume of work carried out, which is a reason for the increase in the state of psychological combustion, and the feeling of accountants to increase the tasks and duties placed on them, and their frustration because of the lack of appreciation of their efforts before Officials. The study also recommended the need to increase the salaries of accountants employed by the Palestinian Ministry of Finance because they are low and not commensurate with the living conditions and the prevailing economic situation in the Gaza Strip, in order to reduce the phenomenon of psychological combustion and raise the level of performance of accountants Key words: Psychological combustion, performance level, Palestinian Ministry of Finance.
Keywords: الكلمات المفتاحية: الاحتراق النفسي، مستوى الأداء، وزارة المالية الفلسطينية. ; Key words: Psychological combustion, performance level, Palestinian Ministry of Finance.